Penerapan Sanksi Adat dalam Penistaan Tempat Suci di Desa Padang Tegal, Kecamatan Ubud, Kabupaten Gianyar - Diah Gayatri Sudibya; Dessy Lina Oktaviani Suendra; Kade Richa Mulyawati (Fakultas Hukum, Universitas Warmadewa, 2021)
Bali is one tourist destination that has high popularity. These tourists really fall in love with the customs and culture that exist in Bali but not a few tourists do not understand the importance of the holy places contained in the tourist attraction area. To protect the holy places that are widely scattered in Bali, it is necessary to have sanctions both in the statutory regulations and in the form of village awig-awig in order to ensnare the perpetrators of defamation of holy places in Bali, but unfortunately this has not been strictly regulated in the existing regulations. The problems raised to be analyzed and answered in this study are 1. How is the application of customary sanctions in defamation of holy places according to positive law? 2. What is the settlement of the case of defamation of holy places in Padang Tegal Village, Ubud District, Gianyar Regency? The method used is an empirical legal research model. Legal products in Indonesia do not regulate defamation of holy places in real terms, the Criminal Code only regulates religious blasphemy and does not mention defamation of holy places. In the case of the defamation of the holy place in Padang Tegal Village, it was resolved with customary sanctions and through a mediation process by the customary Bendesa of Padang Tegal Village with the perpetrators. But unfortunately this customary sanction does not provide a deterrent effect on the perpetrators and only restores the sanctity of the holy place itself.